The RNA-binding protein ELAV regulates Hox RNA processing, expression and function within the Drosophila nervous system - Rogulja-Ortmann, Ana (The Company of Biologists, 2014)
The regulated head-to-tail expression of Hox genes provides a coordinate system for the activation of specific programmes of cell differentiation according to axial level. Recent work indicates that Hox expression can be regulated via RNA processing but the underlying mechanisms and biological significance of this form of regulation remain poorly understood. Here we explore these issues within the developing Drosophila central nervous system (CNS). We show that the pan-neural RNA-binding protein (RBP) ELAV (Hu antigen) regulates the RNA processing patterns of the Hox gene Ultrabithorax (Ubx) within the embryonic CNS. Using a combination of biochemical, genetic and imaging approaches we demonstrate that ELAV binds to discrete elements within Ubx RNAs and that its genetic removal reduces Ubx protein expression in the CNS leading to the respecification of cellular subroutines under Ubx control, thus defining for the first time a specific cellular role of ELAV within the developing CNS. Artificial provision of ELAV in glial cells (a cell type that lacks ELAV) promotes Ubx expression, suggesting that ELAV-dependent regulation might contribute to cell type-specific Hox expression patterns within the CNS. Finally, we note that expression of abdominal A and Abdominal B is reduced in elav mutant embryos, whereas other Hox genes (Antennapedia) are not affected. Based on these results and the evolutionary conservation of ELAV and Hox genes we propose that the modulation of Hox RNA processing by ELAV serves to adapt the morphogenesis of the CNS to axial level by regulating Hox expression and consequently activating local programmes of neural differentiation.